2022
DOI: 10.1161/svin.121.000228
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Thrombectomy in Patients With Acute Ischemic Stroke With Simultaneous Multivessel Occlusions

Abstract: BACKGROUND Simultaneous multivessel occlusions (MVOs) are a rare condition, which may be encountered during endovascular thrombectomy (EVT) for acute ischemic stroke. This study aimed to investigate the prevalence, associated factors, and outcome of patients with acute ischemic stroke and MVO who underwent EVT. METHODS Consecutive patients with acute ischemic stroke who received EVT between September 2014 and April 2021 were included. Acute MVO was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Previous studies also observed worse functional outcome in MVO patients. [1][2][3][4][5] A Swiss multicenter study that reviewed 6081 EVT patients found that of 21 MVO patients, only 20% reached functional independence at 90 days, fairly similar to 13% in our study. 2 A Taiwanese, multicenter study of 602 EVT patients with 11 MVO patients, reported a mortality rate of 54% at 90 days for MVO patients.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Previous studies also observed worse functional outcome in MVO patients. [1][2][3][4][5] A Swiss multicenter study that reviewed 6081 EVT patients found that of 21 MVO patients, only 20% reached functional independence at 90 days, fairly similar to 13% in our study. 2 A Taiwanese, multicenter study of 602 EVT patients with 11 MVO patients, reported a mortality rate of 54% at 90 days for MVO patients.…”
Section: Discussionsupporting
confidence: 86%
“…In the current literature, the reported prevalence of MVO among large vessel occlusion stroke patients ranges between 0.35% and 10.7%. [1][2][3][4][5] Importantly, when multiple vascular territories are involved, compensatory collateral circulation may be affected, leading to expedited infarction and worse functional outcome. Also, compared to single-territory infarcts, infarctions in multiple vascular territories are associated with an increased risk of recurrent stroke, and with etiologies such as cardioembolism, malignancy, and possibly coronavirus disease 2019.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous MVOs are rare conditions but devastating diseases, which may be encountered during MT for AIS ( 7 ). The prevalence of MVOs is 0.34–2.0% in patients with AIS who underwent MT ( 2 , 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous MVOs are rare conditions but devastating diseases, which may be encountered during MT for AIS ( 7 ). The prevalence of MVOs is 0.34–2.0% in patients with AIS who underwent MT ( 2 , 7 ). Most simultaneous MVOs are caused by cardioembolic origin or artery-to-artery embolism ( 2 , 4 ).…”
Section: Discussionmentioning
confidence: 99%